Beberapa Ikon Tantrayana dari Padang Lawas dan Cerminan Ritualnya - Ery Soedewo (Balai Arkeologi Sumatera Utara, 2009)
AbstractIn its heyday, the Padanglawas site area was the center of civilization of Tantric Buddhism. Various Tantric Buddhism rites are reflected in a number of icons found in that area.